Smart Village Concept And Improvement Of Public Services In Indonesia - Devianty, Tia; Hastika, Nunung; Santosa, Pandji (Dinasti Research, 2025)
The Smart Village concept in Indonesia seeks to integrate information and communication technology (ICT) into rural development to enhance public service efficiency, community empowerment, and overall quality of life. This study adopts a qualitative descriptive approach through document analysis to explore the implementation of Smart Village initiatives as a strategy to reduce disparities between urban and rural areas. Key challenges identified include infrastructure gaps, limited digital literacy, budget constraints, resistance to change, and data security concerns. Successful case studies such as Banyuwangi’s Smart Kampung, public-private partnerships in Pangandaran, and the adoption of telemedicine and e-learning platforms illustrate significant improvements in administrative efficiency, transparency, healthcare access, education, and local economic empowerment. The findings emphasize the importance of multi-stakeholder collaboration involving government, private sector, academia, and communities to overcome these barriers. Furthermore, the study outlines the phased process of digital transformation in public services: digitization, digitalization, integration, and intelligent governance, exemplified by initiatives such as e-KTP, the Village Information System (SID), and the One Data Indonesia portal. Policy frameworks including the National Electronic-Based Government System Architecture (SPBE) and the Digital Village Movement are identified as critical enablers. Ultimately, equitable infrastructure, comprehensive digital literacy, secure data governance, and sustainable funding models are essential to scale Smart Village initiatives nationwide, fostering inclusive and sustainable rural development.